The Characteristics And Rationality Of Treatment Of Diabetic Neuropaty In Elderly With T2DM At Private Hospital X In Denpasar On March-May 2021 - Putrawan, Ida Bagus Indra Shadnyana; Indrayani, Agung Wiwiek; Mahendra, Agung Nova; Dewi, Ni Wayan Sucindra (E-Jurnal Medika Udayana; Vol 11 No 6 (2022): E-Jurnal Medika UdayanaDO - 10.24843/MU.2022.V11.i06.P13, 2022)
Diabetic neuropathy (ND) is the very common complication caused by type 2 diabetes mellitus (DM), DM is an epidemic in the elderly group. Elderly can be defined as someone that has come to the age of > 60 years and is said to have entered the final stage of the life phase. The aging process experienced by the elderly is cued by the phase of reduction in many functions of the body's organs called degenerative. This special conditions experienced by the elderly are accompanied by several diseases or complications so that they get relatively many types of drugs called polypharmacy, this causes a clinician to consider giving treatment to the elderly in order to minimize the side effects or toxic effects of a drug. This research aims to specify the characteristics and rationality of treatment for diabetic neuropathy in the elderly. This research is a quantitative descriptive study with a cross sectional design. In this study using purposive sampling technique with a sample size of 110 samples taken at the neurology polyclinic of the private hospital x in Denpasar. All samples were processed using SPSS 22.0 and Microsoft Excel and obtained 7 types of drugs and the most drug use are 55 (50%) of gabapentin with vitamin B complex as adjuvant therapy as many as 102 (92.7%) and 106 (96.3%) ) sample received more than 1 drug. In this study, the treatment given is a rational drug choice to treat ND in the elderly.